Pengaruh Pemasaran Digital Dan Kualitas Produk Terhadap Keputusan Pembelian Melalui Kepercayaan Merek Pada Toko Wardah Di Buaran Mall: Pengaruh Pemasaran Digital Dan Kualitas Produk Terhadap Keputusan Pembelian Melalui Kepercayaan Merek Pada Toko Wardah Di Buaran Mall - Willdanny, Putri Zulia; P.Sukma , Rivera (Ekonomi & Bisnis, 2024)
This research aims to understand the influence of digital marketing and product quality on purchasing decisions through brand trust at the Wardah store in Buaran Mall. Data was collected by distributing questionnaires to 225 respondents, using Purposive Sampling techniques and data were analyzed using Structural Equation Modeling (SEM) via PLS version 3.0 software. The results show that the influence of digital marketing has a positive impact on brand trust. Digital Marketing does not have a positive and significant impact on purchasing decisions. Product quality has a positive and significant impact on brand trust. Product quality has a positive and significant impact on purchasing decisions. Brand trust has a positive and significant impact on purchasing decisions Keywords: digital marketing, product quality, brand trust, purchase decision